Nine lives : a novel - Swanson, Peter, 1968- (William Morrow, an Imprint of HarperCollins Publishers, 2022)
"From the New York Times bestselling author of Eight Perfect Murders comes the heart-pounding story of nine strangers who receive a cryptic list with their names on it-and then begin to die in highly unusual circumstances"--